Early detection and management of white uust disease (Albugo candida) in rapeseed-mustard (Journal of Oilseed Brassica, 2026)
The early detection of Albugo candida was done by PCR-based assay and light microscopy. In PCR based assay the primers ITS1 (3’-GAGGGACTTTTGGGTAATCA-5’) and Short ITS JV34 (3’-CGCCATTTAGAGGAAGGTGA-5’) and JV37 (3’-GTCAAGCAAAACAT-5’) were used to amplify the ITS region of A. candida and Alternaria brassicae. PCR amplification of A. candida from inoculated symptomatic and asymptomatic leaves yielded PCR products of 1200 bp and 600 bp of ITS1 and Short ITS primers, respectively whereas no bands were amplified in A. brassicae. This confirmed the presence of A. candida in asymptomatic inoculated leaves at early stages i.e. 1, 2, 3, 4, 5 and 6 days after inoculation (DAI). In light microscopy the presence of pathogen structures were observed from inoculated symptomatic and asymptomatic inoculated leaves. The presence of pathogen structure viz. mycelium and sporangia was observed in asymptomatic leaves at early stages i.e. at 6,7,8 and 9 DAI ,in symptomatic leaves at 10 and 11 DAI and no fungal structures in healthy mustard leaves after staining with 1 percent cotton blue in lacto phenol and 0.4% trypan blue. During evaluation of rapeseed-mustard germplasm it has been observed that some Brassica germplasm escaped from the white rust disease in field found susceptible in glasshouse at both the stages (EC-399299) or only at true leaf stage (Katili local, Eruca sativa, Basanti and Banarasi rai, PWR-14-8, PWR-14-9, PWR-14-10, PWR-14-11, RMT-1-10-1, IC 597942 and IC265495). The study revealed that for the confirmation of resistant sources, it is very essential to evaluate Brassica germplasm first in field and then in glasshouse at both the stages i.e. at cotyledonary and true leaf stage under high disease pressure. Among various fungicides Metalaxyl 8% + Mancozeb 64% (Ridomil MZ @ 0.25%) and a biological origin Azoxystrobin (Amistar 25 EC @ 0.1%) were found highly effective in inhibiting sporangial germination in-vitro and in controlling white rust disease (no occurrence of disease) in glasshouse and in field.